Adaptação transcultural e evidências de validade de um instrumento para avaliação da disfunção sexual em homens brasileiros com sintomas do trato urinário inferior - André Carlos Santos Ferreira (2023)
Introduction: Lower urinary tract symptoms (LUTS) can have negative effects on people's daily lives, as they can compromise quality of life, interfere with sexual satisfaction and increase the likelihood of depressive disorders. With aging, urinary symptoms become more common, and may be related to sexual problems such as erectile dysfunction. These complaints have a significant impact on both individual and collective health, and generate high health care costs. Sexual dysfunction (SD) and LUTS are manifestations that often coexist in men. In this context, the importance of using measuring instruments with evidence of validity to assess the severity of the dysfunction is emphasized, since these tools have the capacity to measure subjective information, and, therefore, are useful in research and clinical practice. Objective: The present study aimed to carry out a cross-cultural adaptation and analysis of the validity evidence of the International Consultation on Incontinence Questionnaire Male Sexual Matters Associated with Lower Urinary Tract Symptoms Module (ICIQ-MLUTSex) used to assess SD in men with LUTS. Method: This is a psychometric study of adaptation and validation of the ICIQ-MLUTSex questionnaire for the Portuguese language spoken in Brazil. The study was carried out in four stages: 1) cross-cultural adaptation of the ICIQ-MLUTSex questionnaire; 2) evidence of content validity of the ICIQ-MLUTSex questionnaire; 3) evidence of validity of the response process of the ICIQ-MLUTSex questionnaire; and 4) evidence of internal structure validity, reliability and evidence of validity in relation to other variables of the ICIQ-MLUTSex questionnaire. It was carried out in an outpatient clinic of a reference hospital in oncology, located in the city of Belo Horizonte, Minas Gerais, Brazil. Twenty specialists from the five Brazilian regions participated in the second stage of the study, 39 individuals with LUTS in the third stage of the study and 138 in the fourth stage. The study was submitted to the Research Ethics Committee of the Federal University of Minas Gerais, being approved under opinion nº 5,287,948. Results: All stages of the cross-cultural adaptation process were satisfactory, from the point of view of linguistic equivalences and the criteria of clarity, practical pertinence and theoretical relevance. The ICIQ-MLUTSex questionnaire has four items that deal with the latent variable and four subsequent items on the impact on quality of life. In the evaluation carried out by the expert committee, the item that deals with erection obtained a CVR = 1.00 in the practical relevance aspect, and the item that deals with pain/discomfort obtained a CVR = 0.473 in the clarity aspect and, therefore, was reformulated. Item scales were restructured to an ordinal format with four response options (1st, 2nd, 3rd and 4th); All recommendations regarding textual content were endorsed by the ICS ICIQ Group. The pre-test stage (evidences of validity of the response process) allowed an overview of the instrument by the target audience and modifications such as: 1) inclusion of the term 'hard penis' in item 1a; 2) exclusion of the term 'sperm' in item 2a and inclusion of the term 'you enjoy'; and 3) inclusion of the term 'when enjoying' in item 3a. The analyzes of the internal structure validity evidence indicated fair factorability for the model analysis, and indication that the ICIQ-MLUTSex is one-dimensional, confirmed by the UniCO (0.99), ECV (0.94) and MIREAL (0.18) indices. It presented high factor loadings and adequate commonalities, demonstrating that the proportion of common variance present is satisfactory, representing 78% of the total explained variance of the instrument, which point to an instrument with evidence of validity of a consistent and reliable internal structure for the measurement of the latent variable. Reliability was measured by Standardized Cronbach's Alpha (α = 0.95) and McDonald's Omega (ω = 0.95), with acceptable values, and with excellent replicability, confirmed by the Construct Reliability - Index GH (0.81). There was a positive correlation between the total score of the ICIQ-MLUTSex questionnaire and the IPSS score (r = 0.67; p < 0.05) and a negative correlation between the total score of the ICIQ-MLUTSex questionnaire and the QS-M score (r= -0.84; p < 0.05), indicating that there is a direct relationship between the variables, confirming the established hypothesis. Conclusion: It is concluded that the Brazilian version of the ICIQ-MLUTSex presents good evidence of content validity, response process, internal structure and relationship with other variables, being recommended its use in the way it is presented, in research and clinical practice, contributing to the expansion of scientific production on this topic, so that actions aimed at improving the quality of life of men with SD can be implemented.